Wastewater treatment efficacy evaluated with in vitro bioassays. (1st December 2020) - Neale, Peta A.; O'Brien, Jake W.; Glauch, Lisa; König, Maria; Krauss, Martin; Mueller, Jochen F.; Tscharke, Ben; Escher, Beate I.
Abstract: Bioassays show promise as a complementary approach to chemical analysis to assess the efficacy of wastewater treatment processes as they can detect the mixture effects of all bioactive chemicals in a sample. We investigated the treatment efficacy of ten Australian wastewater treatment plants (WWTPs) covering 42% of the national population over seven consecutive days. Solid-phase extracts of influent and effluent were subjected to an in vitro test battery with six bioassays covering nine endpoints that captured the major modes of action detected in receiving surface waters. WWTP influents and effluents were compared on the basis of population- and flow-normalised effect loads, which provided insights into the biological effects exhibited by the mixture of chemicals before and after treatment. Effect removal efficacy varied between effect endpoints and depended on the treatment process. An ozonation treatment step had the best treatment efficacy, while WWTPs with only primary treatment resulted in poor removal of effects. Effect removal was generally better for estrogenic effects and the peroxisome proliferator-activated receptor than for inhibition of photosynthesis, which is consistent with the persistence of herbicides causing this effect. Cytotoxicity and oxidative stress response provided a sum parameter of all bioactive chemicals including transformation products and removal was poorer than for specific endpoints except for photosynthesis inhibition. Although more than 500 chemicals were analysed, the detected chemicals explained typically less than 10% of the measured biological effect, apart from algal toxicity, where the majority of the effect could be explained by one dominant herbicide, diuron. Overall, the current study demonstrated the utility of applying bioassays alongside chemical analysis to evaluate loads of chemical pollution reaching WWTPs and treatment efficacy. Graphical abstract: Image 1 Highlights: Ten wastewater treatment plants studied covered 42% of the Australian population. Effect removal efficacy assessed using a battery of in vitro bioassays. Chemical and in vitro mixture effect loads were very similar in all WWTP influents. Removal efficacy was far higher for secondary WWTPs compared to primary WWTPs. Ozonation most efficiently removed effects apart from oxidative stress response.